2000
DOI: 10.4049/jimmunol.164.6.3274
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell Priming Accelerates the Clearance of Sendai Virus in Mice, but Has a Negative Effect on CD8+ T Cell Memory

Abstract: Current vaccines designed to promote humoral immunity to respiratory virus infections also induce potent CD4+ T cell memory. However, little is known about the impact of primed CD4+ T cells on the immune response to heterologous viruses that are serologically distinct, but that share CD4+ T cell epitopes. In addition, the protective capacity of primed CD4+ T cells has not been fully evaluated. In the present study, we addressed these two issues using a murine Sendai virus model. Mice were primed with an HN421–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…A complete understanding of the cellular responses to M. tuberculosis will require knowledge of the T cell responses to many different Ags. Indeed, if a large proportion of the T cells recruited to the lung are M. tuberculosis specific, our data indicate that T cells that recognize many different Ags are involved in the response, because only 2% of the population recognized ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Information regarding the full spectrum of Ags recognized will be critical for the evaluation of different vaccination strategies, because candidate vaccines might vary in their abilities to elicit responses to particular protective Ags.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete understanding of the cellular responses to M. tuberculosis will require knowledge of the T cell responses to many different Ags. Indeed, if a large proportion of the T cells recruited to the lung are M. tuberculosis specific, our data indicate that T cells that recognize many different Ags are involved in the response, because only 2% of the population recognized ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Information regarding the full spectrum of Ags recognized will be critical for the evaluation of different vaccination strategies, because candidate vaccines might vary in their abilities to elicit responses to particular protective Ags.…”
Section: Discussionmentioning
confidence: 99%
“…Lung T cells were stimulated in vitro with ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , and BrdU and IFN-␥ were measured simultaneously as described above. Only 11% of the ESAT-6 1-20 /IA b -specific CD4 T cells incorporated BrdU on day 125 (Fig.…”
Section: Turnover Of Ag-specific T Cellsmentioning
confidence: 99%
“…In addition to providing B and T cell help, peptide-primed CD4 ϩ T cells can enhance viral clearance by an Ab-independent mechanism that is mediated in part by IFN-␥ (3,4). Interestingly, a recent study has shown that CD4 ϩ memory cells in lymphoid tissues are relatively unstable and decline progressively following the resolution of a viral infection (5).…”
Section: D4mentioning
confidence: 99%
“…These data have important implications for vaccination, because priming CD4 ϩ T cells with peptides can reduce the numbers of CD8 ϩ memory cells generated during viral infection (3,4), in essence replacing relatively stable CD8…”
Section: Cells the Numbers Of Virus-specific Cd4mentioning
confidence: 99%
“…[27][28][29] Despite the potential complexity of antiviral T-cell responses, the recognition of virus both in mouse models and in humans is often highly focused on a small number of epitopes, making peptide-induced tolerance a realistic possibility. [30][31][32] Immunological tolerance may act through a number of different mechanisms, including deletion of reactive clones, anergy through incomplete or altered signalling and regulation by regulatory T cells. Here we evaluate the impact of inducing intranasal tolerance to the CD4 and CD8 immunodominant T-cell epitopes of SeV on gene expression following repeated administration to the airways.…”
Section: Introductionmentioning
confidence: 99%